Student Teachers Learning to Teach: The Mastery and Appropriation of Digital Technology - Trond Haugerud (Universitetsforlaget, 2011)
This article aims to shed light on the processes by which student teachers change and shape their understanding of ICT (Information and Communication Technology) as a tool for learning. Two types of processes are investigated. One is the process by which student teachers gain a technical proficiency, i.e. how student teachers benefit from their technical skills in a school context. The other process is concerned with how student teachers are able to integrate or combine a technical proficiency with a broader view on how teaching and learning should be conducted. The research reviewed indicates that an isolated technical proficiency is not sufficient for providing new teaching opportunities, and there seems to be a gap between technical knowledge and knowledge on how to employ technology in a learning context. In this light, student teachers need to develop a view on ICT that goes beyond the mere technical aspects. The concepts "mastery" and "appropriation" from Wertsch (1998) are employed to structure the discussion. These two concepts from Wertsch can inform us about the way in which student teachers approach ICT as a tool for learning and can help characterize this approach.